FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA PEMBAYARAN KONSUMEN DI CV ANUGERAH UTAMA KOTA GORONTALO - Trisusanti Lamangida; Sri Hantuti Paramata; Illiyin Laya (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2018)
This research was conducted at CV Anugerah Utama Gorontalo City. The aim of the research was to know the factors that causes of bad credit on consumer payments, also to find out the effort of resolving bad credit. Lending redit certainly cannot be separated from risks, one of them is bad credit which will affect consumer payments. Therefore, CV Anugerah Utama should apply credit analysis. The factors that causes of bad credit are Character, Capacity, Capital, Collateral, and Condition. The method used in this research was qualitative by structured interviews. The results of this research shows that CV Anugerah Utama has implemented credit analysis compatible to Standard Operating Procedures (SOP) and applicable requirements. The main factors that causes of bad credit on consumer payments is Character. And the efforts of resolving bad credit are Rescheduling, Reconditioning, and Guarantee Execution.Keywords: Consumer, Bad Credit